THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON CAPITAL STRUCTURE OF MANUFACTURING COMPANIES LISTED ON IDX IN 2016-2018 - Kevin Senjaya; Lidya Agustina (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2020)
This study aims to determine the internal and external factors of the company's capital structure. The variables in this study consisted of profitability (X1), liquidity (X2), solvency (X3), tangibility (X4), sales growth (X5), inflation (X6), tax (X7), USD exchange rate (X8), and capital structure (Y). The population in this study is the manufacturing companies in the goods and consumption industry sector which are listed on the Indonesia Stock Exchange in 2016-2018. The sample in this study was chosen based on the purposive sampling method, resulting in 76 companies as much data. This study uses secondary data and the analysis technique used is multiple linear regression. The results of this study indicate that profitability, solvency, tangibility, and tax affect the company's capital structure, while liquidity, sales growth, inflation, and the USD exchange rate do not affect the company's capital structure